2020
DOI: 10.1038/s41416-020-1009-1
|View full text |Cite
|
Sign up to set email alerts
|

The significance of highlighting the oestrogen receptor low category in breast cancer

Abstract: The latest ASCO/CAP guideline has recommended to report oestrogen receptor (ER) low cases (ERlo; 1–10%) as “ER low positive category”, prompting us to compare the clinicopathologic features, biomarkers, survival and treatment of the ERlo cases with other subgroups (ER negative (ERneg) and ER high (ERhi)). ERlo cases revealed more similar clinicopathologic and biomarker profiles (including younger age, larger tumour, high proliferation, HER2 and basal markers expression) to ERneg than ERhi cancers. The ERlo cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…Compared with ER‐high cases, ER‐low cases were associated with higher grade, more necrosis, more stromal tumor‐infiltrating lymphocytes, and higher expression of Ki67, HER2, EGFR, and CK5/6. Compared with ER‐negative cases, ER‐low cases were associated with higher PR but lower grade, lower expression of CK5/6 and CK14 [ 53 ]. These findings indicated distinct and heterogeneous behavior of ER‐low tumors, with some resembling ER‐negative tumors biologically.…”
Section: Molecular Essencementioning
confidence: 99%
“…Compared with ER‐high cases, ER‐low cases were associated with higher grade, more necrosis, more stromal tumor‐infiltrating lymphocytes, and higher expression of Ki67, HER2, EGFR, and CK5/6. Compared with ER‐negative cases, ER‐low cases were associated with higher PR but lower grade, lower expression of CK5/6 and CK14 [ 53 ]. These findings indicated distinct and heterogeneous behavior of ER‐low tumors, with some resembling ER‐negative tumors biologically.…”
Section: Molecular Essencementioning
confidence: 99%
“…However, the benefit of endocrine therapy for tumors staining ER positive 1%–10% (ER-low) remains controversial. Recent studies suggested ER-low patients as a heterogeneous category, whose clinical behaviors and molecular profiles appears more similar to those of ER-negative breast cancers [ [10] , [11] , [12] , [13] ]. Due to the low frequency of this subgroup, there is limited evidence on endocrine responsiveness of ER-low patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that treatment options for ER − tumors may be appropriate for some ER low tumors; however, endocrine responsiveness of primary breast cancer patients with low ER expression needs to be further explored in prospective studies. 20 This study has certain limitations. First, the study was limited by its retrospective design, and treatment options were not assigned in a randomized manner.…”
Section: Discussionmentioning
confidence: 91%
“…Compared to ER high , ER low breast cancer is associated with younger age, advanced stage, larger tumor size, higher HER2 expression, and lower PR expression. 19,20 When morphologically analyzed, ER low tumors exhibit features previously described for basal-like and triple-negative tumors, including higher grade, higher proliferation index, sheet-like growth pattern, intratumoral lymphocytic in ammatory in ltrate, and necrosis. 12 In our current study, we focused speci cally on early stage breast cancer, a novel approach not presented in previous literature.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation